2017
DOI: 10.1021/acsami.7b09608
|View full text |Cite
|
Sign up to set email alerts
|

Zwitterionic Manganese and Gadolinium Metal–Organic Frameworks as Efficient Contrast Agents for in Vivo Magnetic Resonance Imaging

Abstract: Two water-stable three-dimensional Mn- and Gd-based metal-organic frameworks (MOFs), {[Mn(Cmdcp)(HO)]·HO} (1) and {[Gd(Cmdcp)(HO)](NO)·3HO} (2, HCmdcpBr = N-(4-carboxy benzyl)-(3,5-dicarboxyl)pyridinium bromide), have been prepared and analyzed. In vitro magnetic resonance imaging indicated that MOFs 1 and 2 possess relaxivity r values of 17.50 and 13.46 mM·S, respectively, which are superior to that of the control Gd-DTPA (r = 4.87 mM·S, DTPA = diethylene triamine pentaacetate). MOFs 1 and 2 also possessed go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 61 publications
0
32
0
Order By: Relevance
“…Besides, Qin et al [80] designed and synthesized two water-stable 3D Mn-based MOF (1) and Gd-based MOF (2) as high-efficiency contrast agents for MRI. Furthermore, in vitro MRI demonstrated that the relaxation r1 of 1 and 2 was 17.50 mM -1 •S -1 and 13.46 mM -1 •S -1 , respectively, which are higher than the r 1 (4.87 mM -1 •S -1 ) of similar Gd-DTPA (DTPA = diethylenetriamine pentaacetate).…”
Section: Paramagnetic Substances (Gd-based/mn-based)mentioning
confidence: 99%
“…Besides, Qin et al [80] designed and synthesized two water-stable 3D Mn-based MOF (1) and Gd-based MOF (2) as high-efficiency contrast agents for MRI. Furthermore, in vitro MRI demonstrated that the relaxation r1 of 1 and 2 was 17.50 mM -1 •S -1 and 13.46 mM -1 •S -1 , respectively, which are higher than the r 1 (4.87 mM -1 •S -1 ) of similar Gd-DTPA (DTPA = diethylenetriamine pentaacetate).…”
Section: Paramagnetic Substances (Gd-based/mn-based)mentioning
confidence: 99%
“…121,139 2), and showed their applications as strong MRI contrast agents under in vivo conditions. 142 The in vitro characterization by MRI demonstrated that Mn-based MOF possessed a slightly higher relaxivity r1 value (17.50 mM -1 •S -1 ) compared with the Gd-based analogue (13.46 mM -1 •S -1 ), and both of them are superior to that of the clinical positive contrast agent, Gd-DTPA (DTPA = diethylene triamine pentaacetate, r1 = 4.87 mM -1 •S -1 ) used as a control in the study (Figs. 13a and 13b).…”
Section: Mn-based Mofsmentioning
confidence: 99%
“…The choice of the ligand is strictly related to increasing the nanoMOF solubility and stability in aqueous environments, while the choice of the MOF network is made with the aim of lowering the Mn II toxicity by encapsulating the metal in the nanoparticles. Due to the presence of Mn II , the MOF shows good R1 relaxivities and T1-weighted images, making this nanoMOF particularly useful as an MRI contrast agent for revealing kidney-related pathologies [81].…”
Section: Mn II -Based Mofsmentioning
confidence: 99%